All‐in‐One Phototheranostics: Single Laser Triggers NIR‐II Fluorescence/Photoacoustic Imaging Guided Photothermal/Photodynamic/Chemo Combination Therapy. (23rd May 2019) - Wang, Qi; Dai, Yeneng; Xu, Jingzeng; Cai, Jie; Niu, Xinrui; Zhang, Lei; Chen, Runfeng; Shen, Qingming; Huang, Wei; Fan, Quli
Abstract: Development of single near‐infrared (NIR) laser triggered phototheranostics for multimodal imaging guided combination therapy is highly desirable but is still a big challenge. Herein, a novel small‐molecule dye DPP‐BT is designed and synthesized, which shows strong absorption in the first NIR window (NIR‐I) and fluorescence emission in the second NIR region (NIR‐II). Such a dye not only acts as a dual‐modal contrast agent for NIR‐II fluorescence and photoacoustic (PA) imaging, but also serves as a combined therapeutic agent for photothermal therapy (PTT) and photodynamic therapy (PDT). The single NIR laser triggered all‐in‐one phototheranostic nanoparticles are constructed by encapsulating the dye DPP‐BT, chemotherapy drug DOX, and natural phase‐change materials with a folic acid functionalized amphiphile. Notably, under NIR laser irradiation, DOX can effectively release from such nanoparticles via NIR‐induced hyperthermia of DPP‐BT. By intravenous injection of such nanoparticles into Hela tumor‐bearing mice, the tumor size and location can be accurately observed via NIR‐II fluorescence/PA dual‐modal imaging. From in vitro and in vivo therapy results, such nanoparticles simultaneously present remarkable antitumor efficacy by PTT/PDT/chemo combination therapy, which is triggered by a single NIR laser. Overall, this work provides an innovative strategy to design and construct all‐in‐one nanoplatforms for clinical phototheranostics. Abstract : Novel single near‐infrared (NIR) laser‐induced multifunctional phototheranostics based on a small‐molecule NIR‐II dye is rationally and successfully developed for effective tumor diagnostic and therapy. Such phototheranostics display encouraging therapeutic effects against tumors, benefiting from the NIR‐II/PA dual‐modal imaging‐guided photothermal/photodynamic/chemo combination therapy, which is triggered by a single NIR laser.